Peran UMKM dalam Meningkatkan Kesejahteraan dan Pembangunan Perekonomian di Indonesia - Dwi Rizqiani Putri; Muhammad Syamsul Hidayat; Muhammad wildan Ilman; Siti Nur Fauziyah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in improving the quality of life and supporting economic growth in Indonesia. MSMEs not only serve as the foundation of the national economy but also contribute significantly to employment, income distribution, and strengthening local economies. This study aims to examine the contribution of MSMEs to the enhancement of welfare and economic development in Indonesia. The research employs a qualitative approach with a deductive strategy based on literature review from various references such as books, reports, and relevant journal articles. The findings indicate that MSMEs have the potential to be a major driver of economic growth, particularly in job creation, income improvement, and maintaining national economic stability, especially during economic crises. Furthermore, MSMEs are characterized by adaptability, local resource-based operations, and their ability to adjust to societal needs. However, MSMEs still face several challenges such as limited capital, low-quality human resources, and inadequate marketing access. Therefore, continuous support from the government and other stakeholders through supportive policies, capacity building, and the utilization of technology is crucial for MSMEs to grow optimally and contribute significantly to national welfare and economic development.